Number of Family Members, a New Influencing Factor to Affect the Risk of Melamine-Associated Urinary Stones - Changjiang Liu; Hui Li; Kedi Yang; Haixia Yang (Tehran University of Medical Sciences, 2013)
Melamine is a new risk of urinary stones. Gansu province is a heavily affected area and has large population and underdeveloped economy. We hypothesized that number of family members and family income may play significant roles in the formation of urinary stones. A case-control study was performed among 190 infants. Results showed that the case group had less numbers of family members than the control (4.4 vs. 5.6, respectively). The multivariate logistic regression analysis indicated that number of family members was an independent influencing factor associated with urinary stones (OR, 0.606; 95% CI, 0.411-0.893; P = 0.011). Family income, however, did not exhibit a significant difference. Observed results suggested that number of family members was a new and significant influencing factor to affect the risk of melamine-associated urinary stones.